Brand–brand relational moments - Ramadan, Zahy B. (2019)
Marketing has evolved from being mainly transactional based to relationship driven. As social media platforms facilitated a two-way communication channel between brands and consumers, they also made it possible for brands to have their own conversations. In fact, such brand–brand conversations are found on Twitter and are increasingly going viral as followers become intrigued and excited around such creative brand exchanges. Interestingly enough, when non-human brands engage in relational moments, they forge even further their brand personalities and become highly anthropomorphized by their followers. These relational moments present high risks and opportunities for companies and are still under-researched. Through a qualitative approach using an inductive thematic analysis to analyze a total of 17,136 comments from brand followers on Twitter, the research studies brand–brand conversations leading to the typology of such relational moments. The findings map six brand–brand relational moments alongside the different inherent strategies, objectives, and desired outcomes from such conversations. This research is among the first to establish the grounds for a brand–brand relationship alongside a typology for such relational moments. While most of the researches focus on relational building between brands and consumers, this research shows that brand–brand relationship moments could be an influencing factor on consumers’ brand perceptions.